LACTOCOCCUS ACIDOPHILUS ЖƏНЕ LACTOCOCCUS PLANTARUM СҮТҚЫШҚЫЛДЫ БАКТЕРИЯЛАРЫМЕН ҰЙЫТЫЛҒАН ТҮЙЕ СҮТІНІҢ ФИЗИКА-ХИМИЯЛЫҚ ҚАСИЕТТЕРІНІҢ ӨЗГЕРУІ (Experimental biology, 2017)
Changes in physical and chemical properties of camel milk fermented by monoculture Lactococcus acidophilus, Lactococcus plantarum strains were istudied. It was shown dynamics of milk parameters such as content of vitamin C, protein concentration, acidity during the fermentation for 6 days.
Keywords: camel milk; Lactococcus acidophilus; Lactococcus plantarum; vitamin C